(untitled) (Architecture Image Studies, 2025)
Storytelling is an inherent aspect of mankind as most of the learning is imparted through it since ages. Stories that are recalled and narrated to others have a greater impact in transferring the knowledge. Native American and Afro-American societies have had the practice of oral tradition in which tales and experiences are passed on from generations to generations based on the memories of the people. Prominent African American author, Toni Morrison has revolutionized the history of Afro-America with her storytelling weapon. With her narrative techniques, she mirrors the repressed realities of her culture. Most of the literature has already existed on Toni Morrison’s works in different themes and concepts. A research gap has identified in Toni Morrison’s two novels particularly God Help the Child (2015) and Home (2012) the concept of radical tool as storytelling is little. Hence, the present research paper digs out on Toni Morrison’s radical tool of storytelling, slave narratives, narrative techniques, repressed memories, trauma, memory & rememory, storytelling as a tool for identity and redemption, memory as a pathway to healing and trauma in the select novels. Through storytelling medium, Morrison has brought the black community into the mainstream of the community with identity and normalize their societal beliefs from African American’s repressed memories. Besides, her narratives also preserve the culture and history of African Americans.